13 Supporting community palliative care resources is vital in the continuing pandemic. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Rawlinson, Fiona; Capel, Margred; Davies, James; Rees, Susan
Abstract : Background: Covid-19 had a dramatic effect on the delivery of health care across all settings: institutions reduced footfall and strict social distancing measures were introduced. Face to face consultations were reduced; referrals to a community palliative care team (CPCT) increased. Referral data was explored for trends in referral patterns that might inform optimal use of resources. Methods: A retrospective notes review was undertaken for referrals received in the first 4 weeks of the pandemic after 'lockdown' in UK. Numbers were compared to 2019. Information was sought on reason for referral and resulting actions. Results: 92 referrals were received, an increase of 26% from 2019. 11 patients died before first assessment, 2 declined a visit because of self isolation and 1, no longer needed CPCT input. 40% referrals were from primary care, 33% from specialty nurses, 13% from palliative care hospital teams, 7% from oncology and 5 others from secondary care. 78% had cancer, 14% - frailty, 5% - dementia and the remainder end stage liver and heart disease. Referral information for the 79 patients reviewed cited pain in 24%, 'support' (not specified) -18%, advance care planning (ACP) mentioned specifically in 14%. Covid 19 affecting usual treatment or follow up plans leading to referral was mentioned in 27%. On first review, 65% needed some aspect of ACP, 43% had pain, 82% had other symptom needs, 15% -ADL needs, 20% - mood problems, 18% care or financial needs, 11% were in the last days of life. Conclusions: Although alternative health care delivery was imperative at the time to ensure hospital capacity, the impact on care delivered by CPCT cannot be underestimated. Referrals increased, 27% appearing to be as a direct result of altered services elsewhere. There is a need to work collaboratively across all settings as future surges of the pandemic progress.